History of western philosophy - Russell, Bertrand (Routledge, 2004)
First published in 1946, History of Western Philosophy went on to become the best-selling philosophy book of the twentieth century. A dazzlingly ambitious project, it remains unchallenged to this day as the ultimate introduction to Western philosophy. Providing a sophisticated overview of the ideas that have perplexed people from time immemorial, it is 'long on wit, intelligence and curmudgeonly scepticism', as the New York Times noted, and it is this, coupled with the sheer brilliance of its scholarship, that has made Russell's History of Western Philosophy one of the most important philosophical works of all time.